Perception and acceptability of bilateral tubal ligation among women attending antenatal clinic at Usmanu Danfodiyo university teaching hospital Sokoto - Yakubu, Ahmed; Sagir, Tukur Dabo; Panti, Abubakar; A., Garba Jamila; Mani, Isah Usman; Funtua, Anas Rabiu; Chappa, Aliyu Muhammed; Markus, Mbakwe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Contraception can be defined as all temporary or permanent measures designed to prevent pregnancy. Bilateral tubal ligation is a surgical and permanent form of contraception offered to women who completed their family size or for limitation of family size due to medical condition. The practices of bilateral tubal ligation is limited in Sub-Saharan African countries, Nigeria inclusive because of great desire for a large family size, cultural and religious factors, misunderstanding and fear of the procedure. The aim of the study was to determine the perception and acceptability of bilateral tubal ligation as a form of contraception among women attending Antenatal clinic at Usmanu Danfodiyo University Teaching Hospital Sokoto. Methods: This was a cross sectional study conducted among women attending antenatal clinic between 1st of May to 31st of July, 2018. The information was obtained using a structured questionnaire to obtain the respondent’s socio-demographic characteristics, questions on perception and acceptability of bilateral tubal ligation. Data analysis was done with statistical package for social sciences version 22 (SPSS Inc, Chicago, IL, USA). Results: The study revealed that 73% of the respondents were aware of bilateral tubal ligation, but only 44% of them have good perception towards it. Majority of the respondents (63.8%) reject BTL for contraception. Most of their reasons were cultural believe (33.3%), regret (31.6%), religious believe (26.6%) and fear of surgery (8.5%). Conclusions: There was poor perception and low acceptability toward bilateral tubal ligation among the study population, mostly due to cultural and religious believes, as well as fear of regret, despite awareness of BTL among majority of the respondents.